An Efficient Cache Organization for On-Chip Multiprocessor Networks - Medhat Awadalla; Ahmed M. Sadek (International Journal of Electrical and Computer Engineering (IJECE), 2015)
To meet the growing computation-intensive applications and the needs of low-power, high-performance systems, the number of computing resources in single-chip has enormously increased. By adding many computing resources to build a system in System-on-Chip, its interconnection between each other becomes another challenging issue. In most System-on-Chip applications, a shared bus interconnection which needs an arbitration logic to serialize several bus access requests, is adopted to communicate with each integrated processing unit because of its low-cost and simple control characteristics. This paper focuses on the interconnection design issues of area, power and performance of chip multi-processors with shared cache memory. It shows that having shared cache memory contributes to the performance improvement, however, typical interconnection between cores and the shared cache using crossbar occupies most of the chip area, consumes a lot of power and does not scale efficiently with increased number of cores. New interconnection mechanisms are needed to address these issues. This paper proposes an architectural paradigm in an attempt to gain the advantages of having shared cache with the avoidance of penalty imposed by the crossbar interconnect. The proposed architecture achieves smaller area occupation allowing more space to add additional cache memory. It also reduces power consumption compared to the existing crossbar architecture. Furthermore, the paper presents a modified cache coherence algorithm called Tuned-MESI. It is based on the typical MESI cache coherence algorithm however it is tuned and tailored for the suggested architecture. The achieved results of the conducted simulated experiments show that the developed architecture produces less broadcast operations compared to the typical algorithm.